O modelo brasileiro de governança acadêmica e seus efeitos na produtividade científica - Barros, Moreno (2014)
Attempt to outline the national context of university governance and academic ethics and to understand the fundamental processes that promote institutional relations in scientific activity in some extent exacerbated by a disjunction between the mission of research, the role of faculty and overevaluation of the publication of articles in scientific journals well classified as premise for obtaining positions and wages in Brazilian universities. New forms of assessments and indicators of academic productivity are presented, especially altmetrics, aiming to revisit the canons of scientific communication and project what we can do to ensure that certain principles are maintained, while appropriate to and designed the way to do science in the 21st century.